Optical Nondestructive UV-Vis-NIR-MIR Spectroscopic Tools and Chemometrics in the Monitoring of Olive Oil Functional Compounds - Lagouri, Vasiliki; Manti, Vasiliki; Gimisis, Thanasis (Olives and Olive Oil as Functional Foods, 2017)
Abstract Spectroscopic methods such as absorption spectroscopy in ultraviolet (UV), visible (Vis), near-infrared (NIR), or mid-infrared (MIR) or their combinations have been used for nondestructive, fast, real-time, off/online monitoring of olive oil quality parameters, and for detection and determination of olive oil adulterants as well as geographic origin. These methods have also been used in the industrial sector to analyze the quality of olive fruit with respect to oil content, moisture, color, and fatty acid content. This chapter considers several applications of UV-Vis-NIR or/and MIR spectroscopy in off/on-line monitoring of olive oil functional compounds and oxidation status in combination with appropriately used spectral preprocessing and data analysis (chemometrics). The UV-Vis-NIR and MIR spectroscopic methods have the advantages of minimal or no sample preparation and the ability of a very simple and rapid simultaneous analysis of several constituents. They constitute one of the most promising and useful on/in-line detection methods for olive oil quality control.
Keywords: chemometrics; fatty acid content; FTIR spectroscopy; MIR spectroscopic method; olive oil functional compounds; olive oil industry; olive oil quality control; spectral preprocessing; UV-Vis-NIR spectroscopic method